TRANSFER PENGETAHUAN PENGENALAN MUSUH ALAMI DAN BIOPESTISIDA PADA KELOMPOK TANI UJUNG PANDANG, DESA BAPEANG, KECAMATAN MENTAWA BARU KOTAWARINGIN TIMUR - Melhanah; Lilies Supriati; Rahmawati Budi Mulyani; Oesin Oemar; Ici Piter Kulu (LPPM Universitas Palangka Raya, 2023)
Bapeang Village, Mentawa Baru Ketapang District, East Kotawaringin Regency produce rice. Pests and diseases that limit the growth of crop are a common problem for farmers as they conduct their farm. Farmers use chemical pesticides to prevent and manage pests and diseases that affect plants such as rice, corn, and long beans. The objective of this community service is to educate farmers about the risks associated with use of chemical pesticides and to offer alternatives that are more environmentally friendly, such as managing naturally occurring pest enemies and their microhabitats and employing biopesticides. Members of Ujung Pandang Farmers Group are the intended audience for the community service projects. The activity takes the form of direct outreach and counseling on the topics: 1) Introduction of natural enemies and their function in plant cultivation; 2) Introduction of Biopesticides, include Botanical Pesticides and Microbial Pesticides; and 3) Discussions on Concept of IPM and Environmentally Friendly Pest and Disease Control. Farmers have a greater understanding of natural enemies of pests and biopesticides, as alternatives to chemical pesticides and are safer and more environmentally friendly, as well as a greater awareness of the risks associated with applying chemical pesticides consistently. The evaluation's findings demonstrate how successfully the activity process has been operating. The attendees were quite engaged in the debate, and the team's presentation of the information contained fresh, previously undiscovered knowledge. This encourages the community service staff to engage with Farmers Group Chairperson to apply the program on cultivated land to ensure its future sustainability.